Effect of mild aerobic training on the myocardium of mice with chronic Chagas disease - Preto E (Dove Medical Press, 2015)
Emerson Preto,1 Nathalia EA Lima,1 Lucila Simardi,2 Fernando Luiz Affonso Fonseca,2,3 Abílio Augusto Fragata Filho,4 Laura Beatriz Mesiano Maifrino1,41Universidade São Judas Tadeu, São Paulo, 2Faculdade de Medicina do ABC, Santo André, 3Universidade Federal de São Paulo, Diadema, 4Instituto Dante Pazzanese de Cardiologia, São Paulo, SP, BrazilBackground: Chronic chagasic heart disease represents extensive remodeling of the cardiovascular system, manifested as cardiac denervation, interstitial mononuclear infiltrate, myocyte and vascular degenerative changes, fibrosis, and hypertrophy. Moreover, aerobic exercises are widely indicated for the treatment of various disorders of the cardiovascular system.Purpose: To evaluate the right and left ventricles of BALB/c mice with chronic Chagas disease, undergoing mild exercise, by using morphometric and stereological methods.Materials and methods: A total of 20 male mice at 4 months of age were used for experiments. The animals were divided into four groups (n=5 in each group): untrained control, trained control, untrained infected (UI), and trained infected (TI). Animals of UI and TI groups were inoculated with 1,000 trypomastigote forms of Trypanosoma cruzi (Y strain), and after 40 days, animals entered chronic phase of the disease. Physical exercise, which included swimming, was performed for 30 minutes daily, five times a week for 8 consecutive weeks at a bath temperature of 30°C. After the trial period, euthanasia and subsequent withdrawal of the heart were done. The organ was prepared by histological staining procedures with hematoxylin–eosin and picrosirius red.Results: We found that the physical training used in our experimental model promoted increase in volume density of capillaries and decrease in volume density of collagen fibers and cross-sectional area of cardiomyocytes in chagasic animals (TI group). By histopathological analysis, we found differences in the inflammatory infiltrate, which was lower in animals of TI group. The training program promoted a recovery of these parameters in the TI group.Conclusion: Our results suggest that low-intensity aerobic exercise acts on morphological and morphometric parameters of the left and right ventricles in mice infected with T. cruzi, reducing the changes caused by the organism and making the results comparable to those of the uninfected control group.Keywords: Chagas disease, myocardium, aerobic exercise, morphometry